2003
DOI: 10.1042/bj20021880
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanism of action of a diketopiperazine inactivator of plasminogen activator inhibitor-1

Abstract: XR5118 [(3 Z,6 Z )-6-benzylidine-3-(5-(2-dimethylaminoethyl-thio-))-2-(thienyl)methylene-2,5-dipiperazinedione hydrochloride] can inactivate the anti-proteolytic activity of the serpin plasminogen activator inhibitor-1 (PAI-1), a potential therapeutic target in cancer and cardiovascular diseases. Serpins inhibit their target proteases by the P(1) residue of their reactive centre loop (RCL) forming an ester bond with the active-site serine residue of the protease, followed by insertion of the RCL into the serpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Plasmin proteolysis must be tightly controlled during tumor angiogenesis, probably to allow vessel stabilization and maturation, substantiating the clinical paradox where by PAI-1 promotes tumor progression, and contraindicating the uncontrolled use of uPA/plasmin antagonists as tumor angiogenesis inhibitors (Bajou et al 2001). Inactivation of PAI-1 might be a potential therapeutic tool in colorectal cancer, and in the last 10 years, PAI-1 has been the target of experimental therapeutic strategies using inhibitors such as XR5118, a diketopiperazine-based low molecular weight inhibitor (Einholm et al 2003), the orally active tiplaxtinin (Leik et al 2006), or polyphenolic inhibitors (Cale et al 2010), which could modulate pharmacologically PAI-1 effects in tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmin proteolysis must be tightly controlled during tumor angiogenesis, probably to allow vessel stabilization and maturation, substantiating the clinical paradox where by PAI-1 promotes tumor progression, and contraindicating the uncontrolled use of uPA/plasmin antagonists as tumor angiogenesis inhibitors (Bajou et al 2001). Inactivation of PAI-1 might be a potential therapeutic tool in colorectal cancer, and in the last 10 years, PAI-1 has been the target of experimental therapeutic strategies using inhibitors such as XR5118, a diketopiperazine-based low molecular weight inhibitor (Einholm et al 2003), the orally active tiplaxtinin (Leik et al 2006), or polyphenolic inhibitors (Cale et al 2010), which could modulate pharmacologically PAI-1 effects in tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, a 41% increase in clot lysis was observed at 5 mg/kg and an infusion doubled the time of vessel occlusion. It was later shown [55] that interactions of XR5118 (12) with PAI-1 inactivate the serpin activity by inducing a different conformation from the one of the latent form. It was suggested that the binding site was in an area between b-sheet A and a-helix F, nearby the one proposed for vitronectin.…”
Section: Diketopiperazines and Analogsmentioning
confidence: 99%
“…These associations have made PAI-1 an attractive pharmaceutical target. However, despite extensive studies, only a few small molecule inhibitors have been identified thus far (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), and the majority of these are poor pharmaceutical candidates as they have relatively low affinity for PAI-1 and are unable to inactivate PAI-1 bound to its plasma cofactor vitronectin.…”
mentioning
confidence: 99%